The continuing search for a better mouse trap: Two tests of a practical, low-cost camera trap for detecting and observing small mammals. - Raymond D Dueser; John H Porter; Nancy D Moncrief (PLoS ONE)
The advent of digital wildlife cameras has led to a dramatic increase in the use of camera traps for mammalian biodiversity surveys, ecological studies and occupancy analyses. For cryptic mammals such as mice and shrews, whose small sizes pose many challenges for unconstrained digital photography, use of camera traps remains relatively infrequent. Here we use a practical, low-cost small mammal camera platform (the "MouseCam") that is easy and inexpensive to fabricate and deploy and requires little maintenance beyond camera service. We tested the MouseCam in two applications: a study of small mammal species composition on two transects across a barrier island and a study of small mammal occupancy along a subtle elevation gradient in a mainland forest. The MouseCam was reasonably efficient, with over 78% of all images containing a recognizable small mammal (mouse, vole, rat or shrew). We obtained an accurate estimate of species composition on the island transects, as indicated by comparison with both concurrent and long-term trapping records for the same transects. MouseCams required a smaller expenditure of personnel and transportation resources than would be required for live trapping. They also detected subtle elevation-related differences in species occupancy in the mainland forest for the marsh rice rat, with the species occurring at lower elevations in the forest. This is consistent with the typical occurrence of the marsh rice rat in marshes and wetlands. We also tested devices (barriers, runways) designed to reduce disturbance by mesopredators (e.g., raccoons). Adding an internal barrier to the MouseCam did not reduce use by white-footed mice, whereas adding an external runway did. We believe specialized small mammal camera-based sensors may have wide applicability in field studies of small mammal distribution, abundance and biology.